Comparative studies of the stability of free and immobilized inulinase from Kluyveromyces marxianus NRRL Y-7571 in aqueous-organic solutions - F. V. A. Risso (Brazilian Journal of Chemical Engineering, 2010)
Enzymes have been extensively used in organic solvents to catalyze a variety of reactions of biological and industrial significance. In this work, the characteristics of free and immobilized inulinase were investigated in buffered solutions of butyl acetate. The influences of the organic solvent content on the optimal temperature and pH, the stabilities to temperature and pH and the kinetic parameters were systematically evaluated. The results showed that the organic solvent content had no effect on the optimal pH, either in the free or immobilized inulinase. For the immobilized enzyme, the optimal temperatures ranged from 55ºC to 60ºC, depending on the content of butyl acetate. At higher butyl acetate content, the stability of the immobilized enzyme increased for both pH and temperature. The organic solvent showed the tendency to increase the values of the kinetic parameters Km and v max for both free and immobilized inulinase.